2002
DOI: 10.1055/s-2002-19533
|View full text |Cite
|
Sign up to set email alerts
|

Kapseldurchbrüche zervikaler Lymphknotenmetastasen: Diagnostischer Stellenwert der Magnetresonanztomographie

Abstract: The specificity (72.2 %) and sensitivity (74.4 %) of MRI examinations to detect extracapsular spread of lymph nodes is only partially satisfying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Moreover, MRI has a poor ability to detect ECS objectively; radiologic–pathologic studies reported a sensitivity of 74% to 80%, specificity of 72% to 78%, and accuracy of 76% to 86% for MRI. 29 , 30 Multivariate analysis showed that ECS failed to show any independent prognostic value after stratification by nodal level, age, sex, T classification, chemotherapy, and necrosis, and was excluded from the proposed N category, in agreement with the study by Li et al 11 …”
Section: Discussionsupporting
confidence: 76%
“…Moreover, MRI has a poor ability to detect ECS objectively; radiologic–pathologic studies reported a sensitivity of 74% to 80%, specificity of 72% to 78%, and accuracy of 76% to 86% for MRI. 29 , 30 Multivariate analysis showed that ECS failed to show any independent prognostic value after stratification by nodal level, age, sex, T classification, chemotherapy, and necrosis, and was excluded from the proposed N category, in agreement with the study by Li et al 11 …”
Section: Discussionsupporting
confidence: 76%
“…Generally speaking, however, the limited sensitivity and specificity of the methods used in relation to the clinical diagnosis of ENE need to be discussed (8). For example, Steinkamp et al showed in several publications a sensitivity of ∼80.9% with specificity of 72.2% for CT investigations and sensitivity of ∼74.4% and specificity of 72.2% for MRI imaging (1,12,13). Clinical diagnosis of ENE by ultrasound, with a sensitivity of 78.6% and specificity of 81.8%, achieved slightly better results than CT or MRI (1,14).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 99%
“…The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 43.7%, 97.7%, 82.6%, 87.3%, and 86.8%, respectively. Steinkamp et al (15) evaluated diagnostic performance of MRI for ENE in 110 patients with HNSCC. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 74.4%, 72.2%, 76.1%, 70.3%, and 73.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%